Screening and identification of multiple antibiotic- resistant genes containing Salmonella Typhi from drinking water: A severe public health concern in Bangladesh - Sohana Akter Mina; Pabitra Debnath; A.K.M Zakir Hossain; Md Zahid Hasan; A.M Masudul Azad Chowdhury (Heliyon)
Contaminated water poses a significant public health risk due to waterborne microbial diseases, with typhoid caused by Salmonella Typhi being the most prevalent bacterial waterborne disease in Bangladesh. This study aimed to assess the presence of antibiotic-resistant genes and their patterns in Salmonella Typhi isolated from drinking water sources in Chattogram City, Bangladesh. Out of 150 samples analyzed, 10 isolates were suspected to be Salmonella Typhi by selective plating and biochemical test and 8 were confirmed using PCR amplification of the fliC gene and subsequent sequencing. Phylogenetic analysis provided insights into the genetic diversity and relationships among the identified isolates. The study revealed the presence of Salmonella Typhi in certain drinking water sources, indicating a potential threat to public health. The presence of antibiotic-resistant genes, including sul2, int1, tem, and gyrA, in the genomic and plasmid DNA of Salmonella Typhi isolates emphasizes the role of contaminated water in spreading antibiotic resistance. All 8 isolates were found to contain at least one antibiotic-resistant gene highlighting the widespread presence of resistance elements. This raises serious concerns about the potential impact on the effectiveness of typhoid treatment. Antibiotic susceptibility testing using the disk diffusion assay confirmed multidrug resistance (MDR) in 87.5 % of the Salmonella Typhi isolates, highlighting the urgent need to address the transmission of antibiotic-resistant genes through drinking water sources. The results confirm the widespread environmental transmission of antibiotic resistance in the region and emphasize the potential consequences for the efficacy of typhoid treatment.